Profil Problem Emosi/ Perilaku Pada Remaja Pelajar SMP-SMA Di Kota Semarang - Ediati, Annastasia (Jurnal Psikologi, 2015)
The aims of this study is to identify the profile of emotional/behavioral problems on adolescents students of junior and senior high school (SMP-SMA) in Semarang, Central Java. The subjects comprised 568 students (grade VII and X; males and females), aged between 13-17 years. Data were collected using the Indonesian translation of the Youth Self Report (YSR). The results of data analysis showed that adolescents in the junior high school/SMP reported emotional/behavioral problems more frequently than the adolescents in the senior high school/SMA (t (566) = 2.08, p = .038), especially in terms of social relations (t (566) = 2.92, p = .004), thought problems (t (566) = 2.47, p = .014), somatic complaints (t(566) = 2.98, p = .002), rule-breaking behavior (t (566) = 6.63, p < .001), and externalizing problems (t(566) = 3,37; p = .001). Gender differences was found in the adolescents’ emotional/behavioral problems. In group of junior high school students (SMP), girls reported more emotional problems than boys (t(335) = -3.55; p < .001), particularly in anxiety/depression (t(335) = -6.51; p < .001); withdrawal (t(335) = -4.26; p < .001), somatic complaints (t(335) = -2.86; p = .004); social problems (t(335) = -3.30; p = .001), attention problems (t(335) = -2.39; p = .017); and internalizing problem (t(335) = -5.76; p < .001). In group of senior high school students (SMA), boys reported more externalizing problems (t(229) = 2.10; p = .037) and rule-breaking behavior (t(229) = 4.44; p < .001) than girls. In contrasts, girls reported more somatic complaints than boys (t(229) = -3.09; p = .001). Adolescents’ emotional/behavioral problems should gained more attention. Preventive as well as curative intervention is needed, particularly intervention that sensitive to gender and age, which also involve significant figures for adolescents (parents, school teachers, and peers).